2003
DOI: 10.1079/pns2002207
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of short-chain fatty acid production

Abstract: Short-chain fatty acid (SCFA) formation by intestinal bacteria is regulated by many different host, environmental, dietary and microbiological factors. In broad terms, however, substrate availability, bacterial species composition of the microbiota and intestinal transit time largely determine the amounts and types of SCFA that are produced in healthy individuals. The majority of SCFA in the gut are derived from bacterial breakdown of complex carbohydrates, especially in the proximal bowel, but digestion of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
1,181
4
26

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,543 publications
(1,242 citation statements)
references
References 20 publications
31
1,181
4
26
Order By: Relevance
“…Notwithstanding, results from our study showed that molar ratios of butyrate released during in vitro fermentation were affected by the RS sources. This might be ascribed to the extent at which substrate is available to microbiota (Jha et al, 2011a), which, in turn, could enhance the proliferation of butyrate-producing bacteria (MacFarlane and MacFarlane, 2003;Pieper et al, 2008). Our results are also supported by findings of Martin et al (2000), where heterogeneous RS sources induced different appearance of butyrate in the portal blood of pigs during a 14 h test period.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Notwithstanding, results from our study showed that molar ratios of butyrate released during in vitro fermentation were affected by the RS sources. This might be ascribed to the extent at which substrate is available to microbiota (Jha et al, 2011a), which, in turn, could enhance the proliferation of butyrate-producing bacteria (MacFarlane and MacFarlane, 2003;Pieper et al, 2008). Our results are also supported by findings of Martin et al (2000), where heterogeneous RS sources induced different appearance of butyrate in the portal blood of pigs during a 14 h test period.…”
supporting
confidence: 90%
“…As the post-hydrolysis RS fractions were characterized by heterogeneous chemistry and structure, different fermentation kinetics may occur. Generally, formation of SCFA depends on several factors such as chemical composition, physical form and availability of specific substrate fermented In vitro fermentation of resistant starch (Brouns et al, 2002;MacFarlane and MacFarlane, 2003), as well as on the microbial population during the fermentation process . Wang et al (2002) reported different SCFA productions in mice from day 3 to day 8 of the experimental period after feeding diets formulated with different types of dietary starches, probably related to a variation in composition and population of indigenous colonic bacteria.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The phyla Bacteroidetes, Firmicutes and Actinobacteria are the most abundant in the pig intestine. The result of fermentation by Bacteroidetes is predominately acetate and propionate, where as butyrate is the primary end product of fermentation by Firmicutes (Macfarlane and Macfarlane, 2003). In this study, LRFI pigs had increased lactobacilli numbers in the caecum compared to HRFI pigs with no differences between the other measured bacteria in either the caecum or colon (P < 0.05; Table 4).…”
Section: Nutrient Digestibilitymentioning
confidence: 52%
“…The principal SCFAs that result from fermentation of both carbohydrates and amino acids are acetate, propionate, and butyrate, although formate, valerate, caproate, and the branched-chain fatty acids formed during the catabolism of branched-chain amino acids (valine, leucine, and isoleucine) are also produced in lesser amounts [34]. It has been reported that germinated barley foodstuff containing protein and hemicellulose significantly increases the concentrations of n-butyrate in normal rats and rats with DSS-induced colitis [35,36].…”
Section: Discussionmentioning
confidence: 99%